Using Mechanoluminescent Materials to Visualize Interparticle Contact Intensity in Granular Media - Pawarut Jongchansitto (2019)
© 2019, Society for Experimental Mechanics. Mechanoluminescent materials have the property of emitting light when they are mechanically deformed. The paper deals with the potential use of these active substances to reveal interparticle contact force networks in granular media under mechanical loading. Preliminary uniaxial tensile tests were first performed on two types of longitudinal specimens for comparison purposes: pure epoxy resin and epoxy resin containing mechanoluminescent powders. Stress-strain curves showed that the powder acted as a reinforcement, but fractographic analysis by SEM revealed that debonding occurred between the epoxy matrix and powder grains during mechanical loading. Various two-dimensional cohesionless granular systems were then studied, using mechanoluminescent cylinders subjected to compression. Whereas uniaxial tensile tests featured homogeneous light emission, localized mechanoluminescence intensities were revealed in the contact zones between cylinders. The study shows that mechanoluminescent materials open perspectives for the identification of interparticle contact intensities in granular media.